METHOD DEVELOPMENT FOR THE ELEMENTAL ANALYSIS OF ORGANIC RICH SOIL SAMPLES BY MICROWAVE PLASMA ATOMIC EMISSION SPECTROMETRY - TÓTH, Csilla Noémi; HARANGI, Sándor; KÁROLYI, Anikó; FÁBIÁN, István; BARANYAI, Edina (Studia Universitatis Babeș-Bolyai Chemia, 2017)
In this study, the method development is described for the multi elemental determination of organic rich soil reference material (BCR 700) by the new microwave plasma atomic emission spectrometry (MP-AES). Two sample preparation methods were compared (open vessel digestion on a hot plate and closed vessel microwave assisted digestion) for the BCR sample and EDTA extraction was carried out. The recoveries were tested by MP-AES and inductively coupled plasma optical emission spectrometry (ICP-OES) method to investigate whether the more cost-effective nitrogen supplied microwave plasma is appropriate for the elemental determination of digested organic rich soil samples. The BCR 700 sample was not certified for digestion methods yet similar sample pretreatment is present in the literature with which a good agreement was found. Our results also correlated with the values provided in the certification of the BCR 700 material for EDTA extraction. It was found that the microwave plasma is an effective and low-cost alternative of ICP-OES for soil analysis and with the convenient atmospheric digestion even the organic rich soil samples can be prepared prior to the elemental determination. However, the microwave assisted digestion is faster and easier to conduct. The limit of detection values of the measured elements by MP-AES are sufficiently low for the micro element determination of soils (Cd 70 µg kg-1, Cr 5 µg kg-1, Cu 25 µg kg-1, Mn 12.5 µg kg-1, Ni 45 µg kg-1, Pb 220 µg kg-1, Zn 155 µg kg-1).